The Pharaoh’s Mummy, SDGs, and Islamic Education: Insights from Dr. Maurice Bucaille - Alwy Ahmed Mohamed; Ahmad Remanda; Mariam Elbanna; Muhammad Ndow; Qudra Bezibweki (Penerbit Hellow Pustaka, 2026)
Objective: This study aims to examine the significance of the discovery and scientific examination of the Pharaoh’s mummy by Dr. Maurice Bucaille as a case study for integrating science and revelation within Islamic education, and to explore its relevance in supporting the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 16 (Peace, Justice, and Strong Institutions). Theoretical framework: The theoretical framework is grounded in the integration of Islamic epistemology (revelation, reason, and empirical observation), the integration–interconnection paradigm, and contemporary perspectives on science–religion dialogue within Islamic education. This framework enables an analysis of how scientific inquiry can reinforce faith-based learning and ethical consciousness. Literature review: Previous studies on Dr. Maurice Bucaille largely focus on his scientific analysis of the Pharaoh’s mummy and his engagement with Qur’anic verses related to history and science. However, limited attention has been given to the educational implications of his work, particularly in relation to Islamic education, curriculum development, and the SDGs. Existing literature highlights the need for educational models that integrate scientific literacy, religious values, and global sustainability agendas. Methods: This research uses an approach that looks at what people have written about before and analyzes documents. It looks at what Bucaille has written about science, what he thinks the Qur'an means, and what people have written about teaching education. The information is looked at to find connections between learning about science, what the Qur'an says, thinking about what's right and wrong, and what people want students to learn about taking care of the earth. This research is really about finding connections between discovery, revelation, ethical reflection, and what people want students to learn about taking care of the earth, which is all part of sustainability-oriented educational objectives, and it is also about Bucaille’s scientific writings and Qur’anic interpretations. Results: The findings show that studying the Pharaoh's mummy and what Dr. Maurice Bucaille says about it is a way to teach people about science and Islamic beliefs at the same time. This helps people think carefully about things, learn about science in a way that is connected to their faith, and understand what is right and wrong. The Pharaoh's mummy study is very useful for education because it helps people learn important things like being a good person and trusting the people who are in charge. This is good for the world because it helps with goals like making sure everyone gets a good education and being a responsible person. The Pharaohs' mummy study is important for education, and it can help with these big goals, like the ones that are part of the Sustainable Development Goals, such as getting a good education and being a good person. Implications: The study shows that Islamic education can use a combination of history and science to help students learn in a way. This means that Islamic education can use stories from scientific facts to teach students important things. Islamic education can help students understand their religion better and learn about taking care of the earth. This way of teaching encourages students to try new things and makes learning more interesting. It also helps students learn by relating things to their lives. It teaches students to think about the ethics of science and how it affects them and the world around them. Islamic education can really benefit from using history and science to teach students. Novelty: The novelty of this research lies in positioning the Pharaoh’s mummy and the work of Dr. Maurice Bucaille as an integrative pedagogical model that bridges science, revelation, and the SDGs, offering a fresh contribution to Islamic education discourse and sustainability-oriented educational reform.